Qualitative Exploration of Factors Impacting Adjustment in Women Survivors of Military Sexual Trauma - (:unkn) unknown (My University, 2018)
This project draws from posttraumatic growth and resilience theories, as well as Critical Discourse Analysis and utilizes multiple case study to offer an in-depth examination of the military sexual assault experiences across eleven cases of women who served in the Marine Corps, Navy, Army, and Air Force from the 1960s to the present-day military. The cross-case analysis revealed a three-stage model of adjustment including adjustment to the military culture, surviving the sexual assault, and surviving the fallout, as well as the internal characteristics and behaviors women relied on to navigate these stages. While the data yielded pockets of strengths within the military context there was a notable lack of consistency among the perceived strengths of the military environment. There was, however, consistency in women’s reports of misogyny and sexism and significant barriers to adjustment created by this pervasive military culture. This project offered an integrated perspective of the interaction of behaviors, environments, and individual characteristics and how these simultaneously result in resilience, distress, growth, and posttraumatic stress and adds to current understandings of MST by offering a description of how the military environment both supported and presented considerable barriers to adjustment for the participants.
Keywords: female veterans; military; MST; resilience; sexual assault; women veterans